Cytotoxicity of Artemisia Vulgaris Essential oil Encapsulated in SLN on Breast Cancer Cell Line (MCF7): Effect of Artemisia Vulgaris on MCF7 - Pooladi, Mehdi; Teimouri, Maryam; Odoumizadeh, Mohsen (Archives of Advances in Biosciences, 2021)
Introduction: Research has revealed that breast cancer is the second most common cancer among women and that the compounds in Artemisia plant have good anti-tumor potential. Nanomaterials significantly increase solubility, stability, and effective drug delivery. The aim of this study was to evaluate the efficacy of Nano-form of Artemisia essential oil in comparison with non-Nano-form in inhibiting MCF7 cells. Materials and Methods: After extracting essential oil from Artemisia Vulgaris plant, nanoparticles containing Artemisia Vulgaris essential oil were synthesized through homogenizer and sonication method. Different properties of nanoparticles including particle size, zeta potential, and morphology were measured. Finally, the toxicity effect of solid lipid nanoparticles containing essential oil on MCF7 cancer cell line was examined adopting MTT technique.Results: The results indicated that tDCS significantly reduced the scores on DDQ and OCDUS in the active tDCS group compared to the sham tDCS group (P<.05). Results: The results of cellular effect of lipid nanoparticles containing Artemisia Vulgaris annua on MCF7 cells showed that increasing the concentration of lipid nanoparticles containing Artemisia Vulgaris essential oil, compared to purified essential oil, reduced the survival rate of MCF7 cells. Conclusions: The findings show that lipid nanocarriers raise the release rate of essential oil compared to pure essential oil. Increase in concentration of lipid nanoparticles containing Artemisia essential oil reduces the survival rate of breast cancer cells. The IC50 obtained for unbaked essential oils and nanoparticles containing essential oils were 1105 and 262 μg/ml, respectively. Thus, it can be concluded that nanoparticle essential oil of this plant is effective in reducing the IC50 of the drug and increasing cytotoxicity.